1769b Socio-demographic and occupational factors associated with suicide among french farmers. (24th April 2018) - Gigonzac, V; Khireddine-Medouni, I; Breuillard, E; Bossard, C; Guseva Canu, I; Santin, G; Chérié-Challine, L
Abstract : Introduction: An excessive risk of suicide mortality among farmers has been observed internationally and in France. However, only few studies tried to explore this issue in terms of socio-demographic and occupational determinants and analyse whether they act as risk or as protective factors. The objective of this study was to investigate associations between suicide mortality and socio-demographic and occupational characteristics in the population of French self-employed male farmers between 2007 and 2011. Methods: The study population included all French male self-employed farmers. Socio-demographic and occupational characteristics were collected from a compulsory social security system for the workers in the agriculture. Causes of death were obtained from the French National Mortality Database. The associations between socio-demographic and occupational characteristics and suicide mortality were examined using a Poisson multivariate regression. Results: Suicide mortality was associated with age between 45 and 54 years (RR 1.60, 95% CI: 1.24 to 2.06), having an individual farm (RR 1.20, 95% CI: 1.02 to 1.42), a farm area of 20 to 49 hectares (RR 1.47, 95% CI: 1.03 to 2.10) and farming as an exclusive activity (RR 1.66, 95% CI: 1.29 to 2.14). Farming in several French regions was associated with a higher risk of suicide, whereas type of farming was not. Discussion: The results highlighted differences in suicide mortality among French male farmers according to their socio-demographic and occupational characteristics. This study provides a better understanding of the suicide mortality among farmers and should help to orientate actions prevention.